How to Reduce Test Anxiety and Academic Procrastination Through Inquiry of Cognitive Appraisals: A Pilot Study Investigating the Role of Academic Self-Efficacy - Krispenz, Ann; Gort, Cassandra; Schültke, Leonie; Dickhäuser, Oliver (Frontiers in Psychology, 2019)
Background and Objectives: Test anxiety can impair learning motivation and lead to procrastination. Control-value theory of achievement emotions (Pekrun, 2006) assumes test anxiety to be a result of students’ appraisals of the testing situation and its outcomes. Modification of cognitive appraisals such as low self-efficacy beliefs is thus assumed to reduce test anxiety and subsequent procrastination. In the present study, we tested the effects of an inquiry-based stress reduction (IBSR) intervention on students’ academic self-efficacy, their test anxiety, and subsequent procrastination in the final stages of an academic term. Design: Longitudinal quasi-randomized intervention control trial. Meth-ods: University students identified worry thoughts regarding a specific and frightening testing situation. Intervention participants (n = 40) explored their worry thoughts with the IBSR method. Participants of an active waitlist control group (n = 31) received the inter-vention after the study was completed. Dependent variables were assessed before and after the intervention as well as at the end of the term. Results: Data-analyses revealed that the IBSR intervention reduced test anxiety as well as subsequent academic procrasti-nation in comparison to the control group. The effect on test anxiety was partly due to an enhancement of self-efficacy. Conclusions: Our findings provide preliminary evidence that IBSR might help individuals to cope with their test anxiety and procrastination.